Bacillus thurinqiensis Cryl proteins toxic effect against Teda solanivora (Lepidoptera: Gelechiidae) - MARTÍNEZ-O., WILSON; URIBE-V., DANIEL; CERÓN-S., JAIRO (Revista Colombiana de Entomología, 2003)
In the last decade, Tecia solanivora Povolny has become one of the most significant pests in Colombian potato growing areas. In the past, T. solanivora control strategies have been developed using chemical pesticides, although recently some alternative biological control and crop management practices have been used. The use of entomopathogenic microorganisms such as baculovirus and bacteria for T. so/anivora control offers a new useful tool for developing an integrated pest management program. Earlier works explored the potential use of Bacil/us thurinqiensis strains in T. so/anivora control. However, Bt Cry proteins specific to this insect have not been yet identified. In accordance with this. we analyzed the specificity of7 Bt Cryl proteins (CrylAa, CrylAb, CrylAc, CrylBa, CrylCa, CrylDa, and CrylEa) toward the first instar T. solanivora larvae. At the same time, we designed an easy and reproducible bioassay method based on the natural diet. Proteins were evaluated at 4 µg/cm2 dose. which was the LC50 of HDl strain. used as a positive control in bioassays. Results showed higher toxicity of CrylAc compared with the other Cryl proteins evaluated. CrylAc caused a 20% average mortality while no more than 7% were obtained with the rest of the proteins. In order to confirm these findings we evaluated HD73 strain which posses only CrylAc and Cry2A genes and recombinant E. coli strain with only Cry2A gene. As we expected, the bioassays indicated high toxicity of HD73 and low toxicity of Cry2A protein, showing average moralities over 70% and below 10%, respectively. Results indicated that CrylAc is specific to T. solanivora, however, it seems that interaction with other proteins enhances CrylAc activity as observed in bioassays with HDl and HD73 strains where Cryl proteins besides CrylAc are present.